Compressive stress-mediated p38 activation required for ERα + phenotype in breast cancer - Munne Pauliina M.; Martikainen Lahja; Räty Iiris; Bertula Kia; Nonappa; Ruuska Janika; Ala-Hongisto Hanna; Peura Aino; Hollmann Babette; Euro Lilya; Yavuz Kerim; Patrikainen Linda; et al. (NATURE PORTFOLIO, 2022)
Breast cancer is now globally the most frequent cancer and leading cause of women's death. Two thirds of breast cancers express the luminal estrogen receptor-positive (ER alpha + ) phenotype that is initially responsive to antihormonal therapies, but drug resistance emerges. A major barrier to the understanding of the ER alpha-pathway biology and therapeutic discoveries is the restricted repertoire of luminal ER alpha + breast cancer models. The ER alpha + phenotype is not stable in cultured cells for reasons not fully understood. We examine 400 patient-derived breast epithelial and breast cancer explant cultures (PDECs) grown in various three-dimensional matrix scaffolds, finding that ER alpha is primarily regulated by the matrix stiffness. Matrix stiffness upregulates the ER alpha signaling via stress-mediated p38 activation and H3K27me3-mediated epigenetic regulation. The finding that the matrix stiffness is a central cue to the ER alpha phenotype reveals a mechanobiological component in breast tissue hormonal signaling and enables the development of novel therapeutic interventions. Subject terms: ER-positive (ER + ), breast cancer, ex vivo model, preclinical model, PDEC, stiffness, p38 SAPK.Reliable luminal estrogen receptor (ER alpha+) breast cancer models are limited. Here, the authors use patient derived breast epithelial and breast cancer explant cultures grown in several extracellular matrix scaffolds and show that ER alpha expression is regulated by matrix stiffness via stress-mediated p38 activation and H3K27me3-mediated epigenetic regulation.